Survey of the oral health conditions of children in the structural city of Brasilia, DF Brazil (Research, Society and Development, 2022)
The dental caries, as a multifactorial disease, is of extreme importance for the epidemiological reality of the Brazilian population. In the disease manifestation process, several determinant factors are involved, which are intrinsically associated with the regional reality of the populations in which they are. The Epidemiology, as a health area, becomes extremely valuable, when valuating these several determinants and characteristics of the populations, it subsidizes actions aimed at solving the various problems that affect them, thus providing better performance of health teams.Through the ICDAS index (International Caries Detection And Assessment) it was evaluated the oral health status of 37 children living in the Structural City in Brasilia, Federal District Brazil, corresponding to a total of 3950 evaluated dental faces and your average age was 6 years old. Of the children evaluated, 15 were clinically free of caries lesions. Caries lesions were more prevalent in females children than in males ones, and in blacks and mulattos, when compared to whites, although the general indexes were inferior to those found in the literature. Although inserted in low income and risk context, the oral health conditions were better than expected, a fact that can be explained by the water fluoridation policy.